(untitled) - Palkova, Silvie (Aura musica, 2020)
The founder of Severacek, teacher, and choirmaster Jirina Uherkova (1930-1989) contributed to the development of choral singing in Liberec and its surroundings. In her work with the top children's choir Severacek, which she founded in 1958, she works with her husband, Milan Uherek (1925-2012).
Keywords: Jirina Uherkova; choirmaster; Milan Uherek; Severacek; choral singing